Adsorptive removal of toxic methylene blue and crystal violet dyes from aqueous solutions using Prunus spinosa: isotherm, kinetic, thermodynamic, and error analysis - Onuk, Elif Burcu; Isik, Birol (SPRINGER HEIDELBERG, 2025)
In this study, it was aimed to use Prunus spinosa L. fruit pulp as an adsorbent zero-waste and low-cost for the removal of toxic methylene blue (MB) and crystal violet (CV) dyes from aqueous solutions. The adsorbent was characterized utilizing FTIR-ATR, SEM, and pHpzc tests. The pHpzc value of the adsorbent is 4.96. According to optimization experiments, the optimum adsorbent dosage was determined as 0.05 g/50 mL for MB and CV dyes, the optimum pH values were determined as approximately 7 for MB and CV dyes, and the optimum contact time was determined as 45 min for MB and 30 min for CV dyes. The Langmuir model has been used to calculate the maximum adsorption capacities of MB and CV dyes at a temperature of 298 K. The obtained values are 59.59 mg/g for MB and 53.19 mg/g for CV. The experimental data for Prunus spinosa L. for both dyes exhibited a pseudo-second-order kinetic model. According to error analyses, the reproducibility and applicability of isotherm and kinetic models were investigated. From thermodynamic results, the enthalpy values were calculated as - 42.04 kJ/mol for MB and - 24.08 kJ/mol for CV dyes, which indicates that the process is exothermic. Also, the Gibbs free energies of MB and CV dyes were determined as - 34.20 kJ/mol and - 32.33 kJ/mol at 298 K, which indicates the process is spontaneous. Research and comparisons with other adsorbents have demonstrated that Prunus spinosa L. is a cost-effective and appealing choice for removing MB and CV dyes from water solutions.
Keywords: Adsorption; Prunus spinosa L.; Methylene blue; Crystal violet; LOW-COST BIOSORBENT; EQUILIBRIUM; WASTE; PEELS; ACID; NANOPARTICLES; Energy & Fuels; Engineering